Demographic Factors Influencing Career Aspirations of Secondary School Students in Kwara State, Nigeria - Lasisi, Adekola Kamil; Alabi, Mutiu Ayofe (Universitas PGRI Semarang, 2024)
The study investigated the demographic factors influencing the career aspirations of secondary school students in Kwara State, Nigeria. A descriptive survey research design was adopted for this study. Five research hypotheses were raised to guide the study. Simple and stratified random techniques were adopted to draw a total of 600 participants across the three senatorial Districts of Kwara State. Gregor and O’Brien’s Career Aspiration Scale-Revised was used with the reliability coefficients of the three subscales ranging between 0.76 and 0.92. t. Test and Analysis of Variance (ANOVA) statistics were used to test the six null hypotheses at a 0.05 significance level. Descriptive statistics were used for the demographic data. The results revealed that students’ career aspirations are influenced by gender, age, ordinal order and socioeconomic status but not by religion. Based on the findings, it was recommended that parents should relate well with their children and have a positive perception towards their ordinal positions. Career guidance/vocational counsellors should assist parents by providing them with information and support. School counsellors should collaborate with other school stakeholders to help students vocationally and educationally.